2011
DOI: 10.1177/0021998311410510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Taguchi method for wear behavior of Al/SiC/B4C composites

Abstract: In this study, the wear behaviors of aluminum matrix composites with an A360 matrix reinforced with silicon carbide (SiC) and boron carbide (B4C) ceramic particles using Taguchi method were investigated. Wear tests of unreinforced aluminum alloy and Al17%SiC and Al17%B4C particles reinforced aluminum composites (Al/17%SiC and Al/17%B4C, respectively) versus AISI316L stainless steel disc were carried out for a dry sliding condition in a so-called a pin-on-disc arrangement. The wear tests were realized at the sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 16 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…Lots of works were completed by researchers to improve the wear resistance of aluminium alloys [6,7]. Recently, many secondary phases have been added into aluminium alloys to fabricate aluminium matrix composites with high wear resistance [8][9][10][11]. Altınkök [12] reported that fine Al 2 O 3 /SiC particles were propitious to the effects on the tribological properties of Al-based composite.…”
Section: Introductionmentioning
confidence: 99%
“…Lots of works were completed by researchers to improve the wear resistance of aluminium alloys [6,7]. Recently, many secondary phases have been added into aluminium alloys to fabricate aluminium matrix composites with high wear resistance [8][9][10][11]. Altınkök [12] reported that fine Al 2 O 3 /SiC particles were propitious to the effects on the tribological properties of Al-based composite.…”
Section: Introductionmentioning
confidence: 99%
“…The ceramic nanoreinforcement particles have a special attention to their outstanding properties such as high strength per density, high melting point, better wear resistance and good corrosion resistance [12]. The properties of aluminium metal matrix composites improve by reinforcing ceramic particles such as SiCp [13], Al2O3 [14], B4C [15], TiB2 [16], AlN [17], and TiC [18]. Among all the ceramic reinforcements, the SiCp ceramic particles reinforced aluminium based composites attain good mechanical properties and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization was performed using GRA and the results indicated that the sliding velocity was the most effective factor among the control parameters on dry sliding wear, followed by the reinforcement percentage, sliding distance, and contact stress. Soy et al [7] studied the wear behaviors of A360 matrix reinforced with SiC and B 4 C ceramic particles using Taguchi method. They have concluded that the type of the material, applied load, and sliding speed exert a great effect on the specific wear rate, at 48.13%, 31.83%, and 8.77%, respectively.…”
Section: Introductionmentioning
confidence: 99%